Effect of intercropping between tropical fodder plants with corn and nitrogen fertilization on soil physical properties - Mattei, Eloisa; de Oliveira, Paulo Sérgio Rabello; Crusciol, Carlos Alexandre Costa [UNESP]; de Moraes Rego, Carlos Augusto Rocha; Piano, Jeferson Tiago; da Silveira, Lucas (Revista de Agricultura Neotropical, 2021)
The use of diversified crop systems within the same area has received attention as an alternative to monoculture and benefits soil and yield. This study evaluates the effect ofnitrogen fertilization and tropicalfodder plants on soil physical properties. The experiment was conducted between October 2017 and January 2020 under randomized blocks design, arranged in a sub-sub plot scheme, with additional control and four repetitions. The plots contained fodder species (Urochloa brizantha and Megathyrsus maximus) intercropped with corn and the additional control (single corn). The subplots comprised the types of fodder plants management (haymaking and grazing), and the sub-sub plots contained the presence or absence of nitrogen fertilization. The following characteristics were evaluated: soil density (Ds), total porosity (Pt), macro (Ma) and microporosity (Mi), and soil resistance to penetration (Rp). After the management, the use of nitrogen (N) in topdressing of fodder plants increased Ma in the 0-0.05 m layer in the first year. Ds was above the critical limit for plant development. However, it tended to reduce. Adopting an integrated crop-livestock system, independently of the fodder species and the type of management used, did not compromise soil physical quality. Thus, it is an excellent alternative to diversity production.
Influência de forrageiras tropicais em consórcio com milho e adubação nitrogenada sobre as propriedades físicas do solo
Keywords: Integrated systems; Porosity; Resistance to penetration; Soil physical quality